2013
DOI: 10.1021/ic402407k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a High-Symmetry Ferrous Polypyridyl Complex: Approaching the 5T2/3T1 Crossing Point for FeII

Abstract: Electronic structure theory predicts that, depending on the strength of the ligand field, either the quintet ((5)T2) or triplet ((3)T1) term states can be stabilized as the lowest-energy ligand-field excited state of low-spin octahedral d(6) transition-metal complexes. The (3)T1 state is anticipated for second- and third-row metal complexes and has been established for certain first-row compounds such as [Co(CN)6](3-), but in the case of the widely studied Fe(II) ion, only the (5)T2 state has ever been documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
212
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(234 citation statements)
references
References 20 publications
20
212
0
Order By: Relevance
“…For conventional Fe II polypyridyl complexes, however, the extremely short-lived MLCT manifold sets a rather harsh limit of <100 fs for the injection time, although ultrafast injection has been reported for other sensitizers 2,19-21 and is also predicted to be feasible for Fe-based arrangements 27,28 . Therefore, research efforts have recently been directed to retarding the MLCT deactivation, mainly through the enhancement of the ligand field strength 29,30 , coupled with fine-tuning of the MLCT energy level, using conventional as well as cyclometallated ligands 17,31 .We have recently demonstrated that the N-heterocyclic carbene (NHC) ligands, as superior σ-donors, can effectively suppress the MLCT deactivation by significantly destabilizing the MC states 32-34 . Here, we take this work to a new level by demonstrating for the first time highly efficient photo-induced electron injection from the lowest-energy 3 MLCT state of a Fe II complex into a nanoporous TiO 2 film.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For conventional Fe II polypyridyl complexes, however, the extremely short-lived MLCT manifold sets a rather harsh limit of <100 fs for the injection time, although ultrafast injection has been reported for other sensitizers 2,19-21 and is also predicted to be feasible for Fe-based arrangements 27,28 . Therefore, research efforts have recently been directed to retarding the MLCT deactivation, mainly through the enhancement of the ligand field strength 29,30 , coupled with fine-tuning of the MLCT energy level, using conventional as well as cyclometallated ligands 17,31 .We have recently demonstrated that the N-heterocyclic carbene (NHC) ligands, as superior σ-donors, can effectively suppress the MLCT deactivation by significantly destabilizing the MC states 32-34 . Here, we take this work to a new level by demonstrating for the first time highly efficient photo-induced electron injection from the lowest-energy 3 MLCT state of a Fe II complex into a nanoporous TiO 2 film.…”
mentioning
confidence: 99%
“…However, because of their preciousness and toxicity, scientists have never stopped searching for alternatives, among which Fe II complexes, as the lighter congener in the periodic table, are obvious candidates due to their shared properties as well as high abundance, environmental inertness and chemical stability 10 . Unfortunately, Fe II complexes suffer from extremely short-lived metal-to-ligand charge transfer (MLCT) states and are deactivated into the photo-inactive metal-centred (MC) states in a 100 fs regime [11][12][13][14][15][16][17][18] , preventing efficient photo-induced electron injection into a semiconductor.…”
mentioning
confidence: 99%
“…Accordingly, the MLCT-state in a structure analogue of [FeL] 2+ is depopulated within few hundreds of femtoseconds [26]. We note in passing that there is much current interest in "taming" of MLCT states, aiming at longer MLCT-state lifetimes [24,59,60]. Laser-flash photolysis is therefore used to drive the SCO equilibrium (Equation (1)) towards the hs-state by means of a short-lived photochemical stimulus.…”
Section: Dft-derived Sco Energies Of [Fel] 2+ and [Fe(tren)py3] 2+mentioning
confidence: 99%
“…In general, however, a chemist will have flexibility to change bite angles, for example through ligand scaffold design, 9 and equilibrium bond lengths via steric interactions. 3,5,60 It is obvious that the bite angle has a drastic effect on the destabilization energy of the model system and Inorg.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…This can be achieved either via changing the character of the donor ligands themselves 8,10,11,32−34 or by changing the geometry of the ligand scaffold around the metal center. 9,35,36 The end goal is to increase the ligand field strength of Fe(II) polypyridines to the point where the ordering of various electronic states mirrors that of their Ru(II) analogues (see Figure 1). …”
Section: Introductionmentioning
confidence: 99%